Android-Based Area Mapping in the Village of Kampunganyar - Banyuwangi - Mohammad Idhom; Budi Nugroho; Eva Yulia Puspaningrum (Future Science)
Kampunganyar is one of the villages located in Glagah District, Banyuwangi Regency. In this village the internet is connected smoothly that can be accessed by anyone. So it has called